2020
DOI: 10.15406/mojes.2020.05.00195
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the effect of noise pollution on rental values of properties in Nigeria

Abstract: The study assessed the impact of noise pollution on rental values of properties in Nigeria. The study adopted a survey research design. Questionnaire was designed to obtain data from the respondents. The close ended questions were used to collect the data. The questionnaire was distributed to respondents through their emails and phone numbers in May, 2020 during the Covid-19 lockdown. The study adopted purposive and convenient sampling technique. The data analysis was based on sixty one questionnaires retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…However, based on the result of the study that noise pollution is 3.1% reduction on the rental value of residential property in the study area as it is shown in column 5 of Table 8. The result is not different from Wokekoro (2020) which revealed that noise pollution reduces rental value by 2.7% of mean rental value in Port Harcourt, Nigeria. The study support the conclusion by Oloruntoba et al (2012) that noise pollution affects quality of life, causing serious health and social problems and suggested that there should be noise level standard in Nigeria for residential neighborhood, rather than using current 8 hour standard of 90 dB which is recommended for indusial layouts.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…However, based on the result of the study that noise pollution is 3.1% reduction on the rental value of residential property in the study area as it is shown in column 5 of Table 8. The result is not different from Wokekoro (2020) which revealed that noise pollution reduces rental value by 2.7% of mean rental value in Port Harcourt, Nigeria. The study support the conclusion by Oloruntoba et al (2012) that noise pollution affects quality of life, causing serious health and social problems and suggested that there should be noise level standard in Nigeria for residential neighborhood, rather than using current 8 hour standard of 90 dB which is recommended for indusial layouts.…”
Section: Resultsmentioning
confidence: 70%
“…Although, the study failed to quantify the level of the effects of noise pollution on property values. Wokekoro (2020) revealed that noise pollution negatively impacts property values. The study recommends the development and enforcement of noise abatement measures to improve urban neighborhood quality and increase property values.…”
Section: Effects Of Noise Pollution On Property Valuementioning
confidence: 99%
“…The work of Akeh, Shehu, Butu and Modu (2018) asserts that rental value of residential property around Airport, is not solely based on the proximity to the airport, factors such as; willingness to live in close proximity to the airport, the level of aircraft noise also greatly influence residential property around airport (Walker, 2016;Wokekoro, 2020;Zambrano-Monserrate and Ruano, 2019). This research therefore, explores the extent to which the aircraft noise at the Maiduguri international airport in the Nigeria affects the rental value of residential properties around the neighbourhood.…”
Section: Thementioning
confidence: 99%